Policy, Politics and Political Science: Presidential Address to the Canadian Political Science Association, Victoria, June 5, 2013. Issue 4 (18th December 2013) - Atkinson, Michael M.
Abstract : Abstract. Political scientists are increasingly studying public policy in interdisciplinary environments where they are challenged by the political and normative agenda of other disciplines. Political science has unique perspectives to offer, including a stress on the political feasibility of policy in an environment of power differentials. Our contributions should be informed by the insights of cognitive psychology and we should focus on improving governance, in particular the competence and integrity of decision makers. The discipline's stress on legitimacy and acceptability provides a normative anchor, but we should not over invest in the idea that incentives will achieve normative goals. Creating decision situations that overcome cognitive deficiencies is ultimately the most important strategy. Résumé. Les politologues étudient les politiques publiques dans des contextes de plus en plus interdisciplinaires, où ils sont remis en question par les préoccupations politique et normatives d'autres disciplines. La science politique a des perspectives uniques à offrir, y compris un accent sur la faisabilité politique des politiques publiques dans un contexte de relations de pouvoir asymétriques. Nos contributions doivent être informées par les idées associées à la psychologie cognitive et nous devrions nous concentrer sur l'amélioration de la gouvernance, et notamment la compétence et l'intégrité des décideurs. L'accent de notre discipline sur la légitimité et l'acceptabilité fournit un point d'ancrage normatif, mais il ne faut pas trop investir dans l'idée que des mesures incitatives permettront nécessairement d'atteindre des objectifs normatifs. Créer des situations de décision qui surmontent les lacunes cognitives des acteurs est finalement la stratégie la plus importante à adopter.